2015
DOI: 10.1007/s00432-014-1897-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of eukaryotic elongation factor 1 alpha-2 is associated with poorer prognosis in patients with gastric cancer

Abstract: Our results showed for the first time that overexpression of eEF1A2 was correlated with worse outcomes in gastric cancer patients, suggesting its critical roles in the carcinogenesis of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…Its high expression has been found in many cancer tissues of the breast, ovary, and lung (24)(25)(26). eEF1A2 was upregulated in gastric cancer and was an independent indicator to predict poor prognosis in patients with gastric cancer (27), but the expression of eEF1A1 in normal and cancerous gastric tissues has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Its high expression has been found in many cancer tissues of the breast, ovary, and lung (24)(25)(26). eEF1A2 was upregulated in gastric cancer and was an independent indicator to predict poor prognosis in patients with gastric cancer (27), but the expression of eEF1A1 in normal and cancerous gastric tissues has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Duanmin et al have shown that the increased expression of eEF1A2 in pancreatic ductal adenocarcinoma was closely associated with nodal metastasis, perineural invasion and worse prognosis [17]. In the study of Yang et al, the over-expression of eEF1A2 was con rmed to be correlated with worse outcomes in gastric cancer patients [29]. Moreover, Kawamura et al reported that the positive expression of eEF1A2 in non-small cell lung cancer indicated poor prognosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…IHC and scoring. The immunohistochemical assay was performed as previously described (19,20). Briefly, H&E-stained slides were screened to identify optimal intratumoral tissue to construct a TMA (Shanghai Biochip Company, Ltd.) before IHC.…”
Section: Rna Preparation and Reverse Transcription-quantitative Polymmentioning
confidence: 99%